Analisis Eklesiologis terhadap Model Insider Movement C5 dalam Perspektif Teologi Reformed - Rendi Risky Laowo (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
The C5 category of the Insider Movement (IM-C5) has sparked ecclesiological debates because it allows followers of Christ from non-Christian religious backgrounds to retain their socio-religious identity while acknowledging Jesus as Savior. This approach is often considered strategic for reaching communities resistant to conventional evangelistic methods, but it also raises serious concerns regarding church boundaries, sacramentology, and doctrinal authority. From a Reformed theological perspective, the church is understood as a community established by the Word and the sacraments; therefore, any form of contextualization must remain consistent with Scripture and ecclesiological principles. This study aims to assess the theological implications of IM-C5 for the identity of the church within the Reformed framework. To address this issue, the research utilizes a qualitative, analytical-descriptive approach that includes library research and a systematic review of both primary and secondary literature. The findings indicate that, although IM-C5 holds strategic value in mission, its practice risks obscuring the identity of the church, weakening the understanding of the sacraments, and relativizing doctrinal authority. The main contribution of this study is the development of an evaluative rubric based on Reformed ecclesiology, which can be used to consistently assess contextualization strategies at both academic and practical levels.